(untitled) (Islamic Sciences Journal, 2023)
This paper deals with explaining the definition of adultery in language and Sharia، the extent of the limit for adultery and the evidence for prohibition. It also shows the limit of the unmarried adulterer in Islamic law and the limit of the married adulterer in Islamic law. The researcher then talked about the limit of adultery in Islamic law، compared to the punishment issued by the Iraqi Penal Code of 1969. A comparative study is conducted and arrived at consequences of both that: If adultery spreads in a nation، then it withers away and its population decreases، and there some scientist who state that adulterers must be stoned for a hundred times and their skin is probably thrown also.